The Influence of Profitability, Leverage, and Company Size on Tax Avoidance - Rahayu, Annisyah Sri; Subiyanto, Bambang; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This research aims to obtain empirical evidence of the influence of profitability, leverage, and company size on Tax Avoidance. This research data uses secondary data using a purposive sampling technique for companies in the infrastructure, utilities, and transportation industrial sector listed on the Indonesia Stock Exchange (BEI) for the 2017-2021 period, totaling 80 companies. The analysis techniques used are descriptive statistics, multiple linear regression, classical assumption testing, hypothesis testing, and the Statistical Product and Service Solution (SPSS) version 25.0 program. The results of the research concluded that the profitability variable (X1) had a positive and significant effect on Tax Avoidance (Y), Leverage (X2) had a negative and significant effect on Tax Avoidance (Y), meanwhile, company size (X3) had a negative and insignificant effect towards Tax Avoidance (Y). It is hoped that the results of this research will be able to help the government and regulators review policies that can reduce the practice of Tax Avoidance and for taxpayers and business actors to be wise in making decisions about implementing Tax Avoidance.